VARIASI BAHASA MAHASISWA GEN Z DI MEDIA SOSIAL: KAJIAN SOSIOLINGUISTIK TERHADAP PRAKTIK KOMUNIKASI DIGITAL - Hafizah; Apriyanti Widiansyah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Abstract This study aims to explore the phenomenon of language variation usage on Instagram social media among university students from a sociolinguistic perspective. The research employed a qualitative descriptive method. Data were obtained from captions or written expressions found on the Instagram accounts of students. Data collection was conducted through documentation, observation, and note-taking techniques. Data analysis was conducted by categorizing the language variations according to Martin Joos's classification and additional classifications due to the large number of findings that could not be categorized under Joos’s model. The results of the study revealed that the language variations used by students include: (1) intimate style, (2) casual style, (3) consultative style, (4) formal style, (5) frozen style, (6) words with shifted meanings (association), (7) words with elided vowels, (8) words formed through improvisation of base words, and (9) newly created words formed by the creativity of Instagram users. Keywords: Gen Z, Language Variation; Social Media; Sociolinguistic; Students